Halbyggeri mellem fag, politik og økonomi - Furdal, Kim (Forum for Idræt, 2004)
Sports hall construction caught between the profession, politics and the purse This article looks at the political processes that from 1948 onwards led to the eventual construction of Aabenraa Swimming Pool and Sports Centre in the period 1971-73. The article concludes that it was the persistent demands of local people effectively supported by sporting organisations that at several crucial points made local politicians work towards the establishment of a swimming pool and in the end of a sports centre. As a result of the very slow political decision-making process, the politicians’ wishes and requirements for a swimming pool were overtaken not only by technological developments but also by the increasing demands of the welfare state for public bathing facilities, and this led in the mid-1960s to a violent schism in the town council. While at the end of the 1950s open air bathing and swimming pools could be regarded as providing the basic framework for elementary swimming instruction to prevent people drowning at the seaside, swimming pools developed during the 1960s into the welfare state’s alternative to public beaches. When in 1968 it at last became possible to unite the different views as to the purpose of the swimming pool, Friluftsloven (the Open Air Act) of the same year ended up playing a central role in the construction and maintenance of the centre. This, combined with ideologically based requirements that sport should be party to financing the construction of sports centres, still plays a decisive role today in determining the degree to which sports associations can make more substantial sporting investments in, for example, competitive sport.